Tectonic control on vein attributes and deformation intensity in fault damage zones affecting Natih platform carbonates, Jabal Qusaybah, North Oman. (May 2019) - Balsamo, F.; Clemenzi, L.; Storti, F.; Solum, J.; Taberner, C.
Abstract: Understanding the factors that control fracture patterns in fault damage zones is fundamental to predicting fault zone permeability in the subsurface. In this contribution, we present outcrop data on vein attributes collected from 26 fault zones (10 strike-slip and 16 normal dip-slip) that cut Cretaceous Natih Formation platform carbonates exposed in the Jabal Qusaybah anticline, North Oman. Faulting occurred during the growth of the salt-cored anticline and progressed initially from dominant strike-slip faults (burial depth ∼3–4 km) to late normal dip-slip faults (burial depth <1–2 km). The displacements accommodated by both kinematic fault types range similarly from 0.1 to 100 m, and damage-zone width increases with displacement at the same rate for both types. Vein aperture (A), height (H), and spacing (S) were measured in vertical cross-sections (n = 10839 data) along fault-perpendicular, linear scanlines across fault damage zones. Data analyses indicate that, as the master slip surface is approached in each fault zone: (1) vein aperture and height generally increase; (2) vein spacing systematically decreases; and (3) deformation intensity, calculated as vein H/S ratio, increases. However, median H/S values calculated in each damage zone do not show a robust correlation with fault displacement. When analyzed collectively across-fault distributions, H/S ratios indicate that deformation intensity (i) in normal dip-slip fault damage zones is greater than in strike-slip fault damage zones; (ii) in strike-slip fault damage zones is symmetrical with respect to the master slip surface; and (iii) is locally asymmetrically distributed with greater deformation intensity in footwall blocks for normal dip-slip faults. Greater deformation in normal dip-slip fault zones is expressed by greater vein height, rather than smaller vein spacing. The main conclusion is that deformation intensity and vein attributes in fault damage zones are primarily controlled by burial stress and fault kinematics, and less importantly by rheological contrasts between layers, rather than local stress induced by fault displacement. Graphical abstract: Image 1 Highlights: Vein attributes (n = 10839 data) were analyzed across 26 fault damage zones. Approaching master slip surfaces, vein aperture and height increase; spacing decreases. Deformation intensity does not increase with greater fault displacement. Deformation intensity in fault damage zones depends on burial stress and kinematics.